Leading policing in Europe : an empirical study of strategic police leadership - Caless, Bryn; Tong, Stephen, 1972- (Bristol : Policy Press, 2016)
Little is known about those at the command end of policing in Europe. This book details unique access to those at the top of Europe's police forces, obtaining detailed comments from more than a hundred strategic police leaders in 22 countries and presenting information about how they are selected for high office, how they are held to account, and what their views are on current and future challenges in policing.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 26, 2015).
Access is available to the Yale community.
Keywords: Police -- Europe; Police administration -- Europe; Leadership